Respostas
respondido por:
0
35 - ( 4 - 1 ) - ( - 2 + 7 )
*Lembrando que o sinal de - antes do parênteses faz com que troquemos o mesmo.
35 - 4 - 1 + 2 + 7
35 - 5 + 9
30 + 9
39
*Lembrando que o sinal de - antes do parênteses faz com que troquemos o mesmo.
35 - 4 - 1 + 2 + 7
35 - 5 + 9
30 + 9
39
respondido por:
0
(4-1) (2+7)
35 - 3 =32 - 9 = 41
a resposta e 41
35 - 3 =32 - 9 = 41
a resposta e 41
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás